2018
DOI: 10.1080/15548627.2018.1491489
|View full text |Cite
|
Sign up to set email alerts
|

The lysosomal membrane protein LAMP2A promotes autophagic flux and prevents SNCA-induced Parkinson disease-like symptoms in the Drosophila brain

Abstract: Act5C: actin 5C; a.E.: after eclosion; Atg5: autophagy-related 5; Atg8a/LC3: autophagy-related 8a; CMA: chaperone-mediated autophagy; DHE: dihydroethidium; elav: embryonic lethal abnormal vision; eMI: endosomal microautophagy; ESCRT: endosomal sorting complexes required for transport; GABARAP: GABA typeA receptor-associated protein; Hsc70-4: heat shock protein cognate 4; HSPA8/Hsc70: heat shock protein family A (Hsp70) member 8; LAMP2: lysosomal associated membrane protein 2; MDA: malondialdehyde; PA-mCherry: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 108 publications
2
83
0
2
Order By: Relevance
“…Previous studies have reported that Lamp2 confers stress resistance against various conditions, including acidosis, oxidative stress and neurodegenerative disorders (Saha, 2012;Damaghi et al, 2015;Qin et al, 2017;Issa et al, 2018) and is recognized as a vital protector against LMP with unclear underlying mechanisms (Geronimo-Olvera et al, 2017;Wiedmer et al, 2017). In our experimental system, OGD treatment caused the decline of Lamp2 and restoration of Lamp2 partially reduced LMP and cell death of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous studies have reported that Lamp2 confers stress resistance against various conditions, including acidosis, oxidative stress and neurodegenerative disorders (Saha, 2012;Damaghi et al, 2015;Qin et al, 2017;Issa et al, 2018) and is recognized as a vital protector against LMP with unclear underlying mechanisms (Geronimo-Olvera et al, 2017;Wiedmer et al, 2017). In our experimental system, OGD treatment caused the decline of Lamp2 and restoration of Lamp2 partially reduced LMP and cell death of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 59%
“…The role of autophagy in ischemia and ischemia/reperfusion injury is still debated. Excessive inhibition of Beclin1 markedly increases cardiomyocyte death in response to hypoxia/reoxygenation injury (Issa et al, 2018). However, it has also been reported that different mechanisms to inhibit autophagy also protect against myocardial ischemia/reperfusion injury (Wu et al, 2018;Yu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…ROS detection in the Drosophila CNS was performed using the dihydroethidium (DHE) dye (Life technologies) following a previously described procedure (117,118). 10-day-old decapitated female flies were exposed to PQ for 90 min with or without (control) 30-min pretreatment with PACAP.…”
Section: Ros Measurementmentioning
confidence: 99%
“…Studies using Drosophila models have established a bewildering list of mechanisms involved in the α-syn pathogenicity. These mechanisms include alterations in the endoplasmic reticulum (ER)-Golgi trafficking and synaptic vesicle formation [ 133 , 134 ], glutathione abundance [ 111 ], glucose metabolism [ 135 ], actin cytoskeleton that leads to impaired mitochondrial dynamics [ 110 ], mitochondrial integrity and function [ 136 ], macroautophagy [ 137 ], and elevated oxidative stress levels [ 138 , 139 , 140 ].…”
Section: Genetic Models Of Sporadic Pdmentioning
confidence: 99%